Enhanced Acetone Sensing Properties Based on Au-Pd Decorated ZnO Nanorod Gas Sensor - Yinfeng Shen; Yiping Liu; Chao Fan; Qudong Wang; Ming Li; Zhi Yang; Liming Gao (Sensors, 2024)
The mature processes of metal oxide semiconductors (MOS) have attracted considerable interest. However, the low sensitivity of metal oxide semiconductor gas sensors is still challenging, and constrains its practical applications. Bimetallic nanoparticles are of interest owing to their excellent catalytic properties. This excellent feature of bimetallic nanoparticles can solve the problems existing in MOS gas sensors, such as the low response, high operating temperature and slow response time. To enhance acetone sensing performance, we successfully synthesized Au-Pd/ZnO nanorods. In this work, we discovered that Au-Pd nanoparticles modified on ZnO nanorods can remarkably enhance sensor response. The Au-Pd/ZnO gas sensor has long-term stability and an excellent response/recovery process. This excellent sensing performance is attributed to the synergistic catalytic effect of bimetallic AuPd nanoparticles. Moreover, the electronic and chemical sensitization of noble metals also makes a great contribution. This work presents a simple method for preparing Au-Pd/ZnO nanorods and provides a new solution for the detection of acetone based on metal oxide semiconductor.